Living in Protected Areas High School Students Attitudes towards Envıronment Accordıng to New Ecologic Paradigm Scale (Datça Sample) - Teyfur, Emine (Fırat University, 2016)
In this research, historical, natural, archaeological, which is considered a protected area of the urban settlements, etc living in. Datça high school students attitudes towards the environment were examined. Quantitative research methods were used in this study. The measurement instrument revised by Dunlap, Van Lierde to, Mertig and Jones which most widely used worldwide in environmental New Environmental Paradigm (NEP) Scale was applied. Scale necessary permits are obtained for use. It has been applied to a total of 3 different schools in Datca town center living 250 high school students in the 2013-2014 academic year. Especially in the range of scores received by all the variables we can say that is dominated by the medium level of awareness (51-59).

Bu araştırmada tarihi, doğal, arkeolojik, kentsel vb. açılardan sit alanı olarak kabul edilen Datça yerleşim yerinde yaşayan lise öğrencilerinin çevreye yönelik tutumları incelenmiştir. Çalışmada nicel araştırma yöntemleri kullanılmıştır. Ölçme aracı olarak 2000’de Dunlap, Van Liere, Mertig ve Jones tarafından revize edilen dünyada çevre konusunda en yaygın olarak kullanılan Yeni Çevre Paradigma (NEP) Ölçeği uygulanmıştır. Ölçek kullanımı için gerekli izinler alınmıştır. Ölçek 2013-2014 öğretim yılında Datça şehir merkezinde yaşayan toplam 3 ayrı okulda bulunan 250 lise öğrencisine uygulanmıştır. Tüm değişkenlere göre alınan puan aralığında özellikle orta bilinç düzeyinin hakim olduğunu söyleyebiliriz (51-59).
Yeni Ekolojik Paradigma Ölçeğine Göre Koruma Alanlarında Yaşayan Lise Öğrencilerinin Çevreye Yönelik Tutumları (Datça Örneği)